2016
DOI: 10.1186/s13018-016-0462-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of fibular for supramalleolar osteotomy in treatment of varus ankle arthritis: a biomechanical and clinical study

Abstract: BackgroundSupramalleolar osteotomy (SMOT) is a well-accepted treatment method for mid-stage varus ankle osteoarthritis (OA). However, few studies have examined the role of fibular osteotomy in SMOT. The objective of the current study was to compare the biomechanical and clinical outcomes of SMOT with and without fibular osteotomy.MethodsEight cadaveric lower legs with 10° varus/valgus SMOT models were tested using a Tekscan ankle sensor. Tibiotalar joint contact with and without fibular osteotomy conditions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…(2) Still consistent with similar studies, the surgeon has performed repeated simulated operations on a digital model before surgery, they must to face difficulties and detail ready prepared ahead of time; at this time the feasibility and perfectness of the preoperative planning are preferable because it is well thought out [24]. (3) Compared with conventional technology, the use of PSI in operation can make the traditional osteotomy and alignment process faster and more accurate; relevant studies have shown that PSI can reduce the number of surgical procedures and fluoroscopies during the operation, and with the help of PSI, many procedures no longer require repeated attempts [11]. (4) Another possible reason is that our team's rich digital orthopedic operation experience [12] provides this new technology with good personnel, technical reserves and execution ability.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…(2) Still consistent with similar studies, the surgeon has performed repeated simulated operations on a digital model before surgery, they must to face difficulties and detail ready prepared ahead of time; at this time the feasibility and perfectness of the preoperative planning are preferable because it is well thought out [24]. (3) Compared with conventional technology, the use of PSI in operation can make the traditional osteotomy and alignment process faster and more accurate; relevant studies have shown that PSI can reduce the number of surgical procedures and fluoroscopies during the operation, and with the help of PSI, many procedures no longer require repeated attempts [11]. (4) Another possible reason is that our team's rich digital orthopedic operation experience [12] provides this new technology with good personnel, technical reserves and execution ability.…”
Section: Discussionmentioning
confidence: 87%
“…Supramalleolar osteotomy (SMOT) is an effective procedure for the treatment of midstage asymmetric ankle osteoarthritis [1][2][3][4]. Related studies have proved that the key factors affecting the postoperative curative effect of SMOT are the postoperative ankle Takakura stage [5], lower limb power line [6] and ankle angles [7]; but SMOT uses conventional operation (CO) method often does not perfectly accomplish these surgical aims leading to some patients have unsatisfactory outcomes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The surgical treatment of ankle osteoarthritis varies according to the stage. In patients with stage II and IIIA ankle osteoarthritis, low tibial osteotomy (LTO) is indicated for correcting the alignment of the lower end of the tibia surface [1][2][3][4][5], whereas total ankle arthroplasty or arthrodesis is generally indicated for patients with end-stage arthropathy (stages IIIB and IV) [6][7][8][9]. Intraarticular deformities may also be treated with total ankle arthroplasty, and distraction arthroplasty is indicated for patients with stage III or IV arthropathy [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The surgical treatment of ankle osteoarthritis varies according to the stage. In patients with stage II and IIIA ankle osteoarthritis, low tibial osteotomy (LTO) is indicated for correcting the alignment of the lower end of the tibia surface [1][2][3][4][5], whereas total ankle arthroplasty or arthrodesis is generally indicated for patients with end-stage arthropathy (stages IIIB and IV) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%